Convergence characteristics between a rodent, the South American lowland paca, and a ruminant, the African water chevrotain: An exemplary case study - (:unkn) unknown (My University, 2017)
The level of convergence between a rodent, the South American lowland paca Cuniculus paca, and a ruminant, the African water chevrotain Hyemoschus aquaticus, is analysed using 231 characteristics belonging to different biological sectors. A convergence index is established based on the degree of rarity of each characteristic in each species compared to other members of its zoological group. Although the divergent characteristics are as numerous as the convergent ones, the two species are globally similar. Convergent characteristics occur in all biological categories, but their rate varies a great deal among them. From internal anatomy and osteology, through behaviour and ecology to the external appearance of the body, convergent characteristics are all the more frequent since the biological category is directly implicated in the adaptation of animals to their external environment (lowland rainforest). However, only the individuals’ characteristics are concerned and not those of their population or social organisation. This could be due to differences between the communities of terrestrial mammals to which they belong.
Keywords: African Research